2018
DOI: 10.14254/2071-789x.2018/11-3/8
|View full text |Cite
|
Sign up to set email alerts
|

Do Education Levels Matter on Indonesian Economic Growth?

Abstract: Arising from the questions "Would all types of human capital affect economic growth identically? And which type of schooling-primary, secondary, or tertiary-should public policy promote?", this study examines the nexus between different educational levels and Indonesia's economic growth over a reference period 1984-2014. During this period, education expansion took place at all three levels of education reflecting structural changes tied within the policies under the Millennium Development Goals (MDG's) as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 24 publications
2
22
0
1
Order By: Relevance
“…Furthermore, a close link to the educational component of human capital is most evident in the countries where intellectual potential has not yet fully developed, such as is the case in European countries (Haseeb et al, 2019). Based on case studies of the dynamics and factors affecting the development of individual countries, Benos & Karagiannis (2016), Kasri (2011), Mendy & Widodo (2018) have confirmed that education level is a significant factor for economic growth. At the same time, complex studies into the impact of the intellectual component of human capital on social and economic development in the form of multifactorial productivity require a multidisciplinary approach in which the links among these objects are emphasised in evaluations.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, a close link to the educational component of human capital is most evident in the countries where intellectual potential has not yet fully developed, such as is the case in European countries (Haseeb et al, 2019). Based on case studies of the dynamics and factors affecting the development of individual countries, Benos & Karagiannis (2016), Kasri (2011), Mendy & Widodo (2018) have confirmed that education level is a significant factor for economic growth. At the same time, complex studies into the impact of the intellectual component of human capital on social and economic development in the form of multifactorial productivity require a multidisciplinary approach in which the links among these objects are emphasised in evaluations.…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…By analysing the impact of sectoral employment differences and accumulated capital at different levels (Formánek, 2019), it is also possible to acquire an understanding of the impact of factors affecting intellectual potential, including educational influences, on the macroeconomic performance indicator GDP per capita (Androniceanu et al, 2019). Mendy & Widodo (2018) also exemplify such possibilities in their study into the impact of different levels of education population. Even more pertinent to our study, Volchik et al (2018) focus specifically on tertiary education.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…An important influence on economic growth has indirect factors, with immediate action: the size of aggregate demand, respectively, the absorption capacity of the internal market; the efficiency of the banking financial system; savings rate and investment rate; the international environment; labor and capital migration; state budgetary and fiscal policy. Among factors of economic growth intellectual potential has increasing influence on social and economic development (Androniceanu et al, 2020;Bilan et al, 2020;Kinnunen et al, 2019;Mendy & Widodo, 2018). Several authors consider that small and medium-sized enterprises are the main contributor to the economic growth (Krisnaresanti et al, 2020;Dvorský et al, 2020;Bilas et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The global trend of recent decades has been not only the increasing influence of universities on economic growth, but also the increase in their number, which has been observed in different countries and, of course, due to the growing need to generate new knowledge, innovate, and build human capital (Valero & Van Reenen, 2019). An assessment of the direct and indirect positive effects of this, which manifested itself in the economy, showed the need to consider the revival of universities as one of the main mechanisms for ensuring economic growth (Mendy & Widodo, 2018). From the perspective of countries and regions, this has drawn attention to ensuring leadership and competitiveness of universities in an increasingly open and competitive global educational services market.…”
Section: Literature Reviewmentioning
confidence: 99%